2015
DOI: 10.3832/ifor1185-008
|View full text |Cite
|
Sign up to set email alerts
|

Seed trait and rodent species determine seed dispersal and predation: evidences from semi-natural enclosures

et al.

Abstract: Citation: Yi X, Wang Z, Liu C, Liu G, 2015. Seed trait and rodent species determine seed dispersal and predation: evidences from semi-natural enclosures. iForest 8: 207-213 [online 2014-08-28] URL: http://www.sisef.it/iforest/contents/?id=ifor1185-008 Communicated by: Massimo FaccoliSeed trait and rodent species determine seed dispersal and predation: evidences from semi-natural enclosures Xianfeng Yi (1) , Zhenyu Wang (1) , Changqu Liu (2) , Guoqiang Liu (2) Seed traits affect seed dispersal by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Rodents may use different strategies (eating in-situ, eating after removal, scatter-hoarding or larder-hoarding) for different seeds depending on seed size, content, amount and storable characters, as well as in different habitat conditions (Russell and Schupp, 1998;Dirzo et al, 2007;Wang and Chen, 2009;Yi et al, 2015). In this study, very few rubber seeds were scatter-hoarded and the removal distance was often less than 10 m, which may result from the rapid germination of rubber seeds (Smallwood et al, 2001).…”
Section: Discussionmentioning
confidence: 80%
“…Rodents may use different strategies (eating in-situ, eating after removal, scatter-hoarding or larder-hoarding) for different seeds depending on seed size, content, amount and storable characters, as well as in different habitat conditions (Russell and Schupp, 1998;Dirzo et al, 2007;Wang and Chen, 2009;Yi et al, 2015). In this study, very few rubber seeds were scatter-hoarded and the removal distance was often less than 10 m, which may result from the rapid germination of rubber seeds (Smallwood et al, 2001).…”
Section: Discussionmentioning
confidence: 80%
“…Preston and Jacobs (2009) have provided solid evidence that nut movement inside the shell does not affect caching by S. niger. Our results suggest the need for in-depth studies on the behavioural response of different food-hoarding animals to seed traits at the species level (Muñoz et al, 2012;Yi et al, 2014). This is crucial for improving our understanding of the interaction between seeds and animals in seed dispersal systems.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have shown that seed trait is one of the most important factors affecting seed manipulation of food-hoarding animals (Vander Wall, 2010;Yi, Wang, Liu, & Liu, 2014). When food-hoarding animals encounter seeds with different traits, they usually make a quick decision whether to eat or remove the seed and where to hoard it, based on evaluation of many factors: size/mass, coat thickness, nutrition content and chemical defences of the seeds (Jacobs, 1992;Jansen, Bongers, & Hemerik, 2004;Lai, Xiao, & Guo, 2014;Steele, Smallwood, Spunar, & Nelsen, 2001;Vander Wall, 1995;Wang & Chen, 2009;.…”
mentioning
confidence: 98%
“…Their decision is influenced by many factors including seed characteristics and environmental variables. Influential seed traits include seed size, nutrient content, defensive secondary chemicals, durability and hardness of seed coat (Forget et al 1998, Jansen et al 2002, Vander Wall 1990, Wang & Chen 2009, Yi et al 2015. Environmental factors include rodent density, seasonal fruit crop and/or availability of alternative food source (Forget et al 1998(Forget et al , 2002Hallwachs 1986, Hoshizaki & Hulme 2002, Jansen et al 2004, Lichti et al 2014.…”
Section: Introductionmentioning
confidence: 99%